Analysis of Pedagogical Technology, Content Knowledge, and Authentic Assessment of Biology Preservice Teachers in Implementing School Field Introduction (ISFI) - Priskila Uli Arta Lumban Tobing; Ely Djulia; Herbert Sipahutar (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
This research describes the educators serve as facilitators who can enhance the efficacy of the learning process. The success is contingent upon the teacher's proficiency in understanding students, the curriculum, instructional methodologies, and assessments to effectively convey scientific information. Consequently, educators must enhance their quality and proficiency to achieve the objectives of Indonesian national education, namely to cultivate the nation's well-being. The National Science Teacher Association delineates three tiers for the preparation of science educators, encompassing biology instructors: preservice (student teacher candidates), novice teachers (induction), and professional teachers. Professional educators must be adequately prepared from the outset, even as student teacher candidates. Technological Pedagogical and Content Knowledge (TPACK) assists educators in enhancing the quality of classroom learning. This research uses quantitative descriptive research that captures information about the cognitive abilities of TPACK and authentic assessments of prospective biology teacher students at Medan State University and the ability to integrate TPACK in the implementation of ISFI II